Experts for sale: Academic consulting as mechanism for knowledge and technology transfer - Mark O. Sellenthin (Hochschule Koblenz - University of Applied Sciences, Fachbereich Wirtschaftswissenschaften, 2012)
Academic consulting is an important mechanism to transfer tacit knowledge as well as facilitates the transfer of codified knowledge, such as patents. However, not all researchers are equally interested in consulting. A lot of researchers refrain from industry collaboration since external involvement in research issues could be regarded immoral according to the traditional Humboldt university ideal. However, external involvement increases through external funding, in particular from industrial sources and the general public demands universities to become more entrepreneurial in order to increase economic growth and welfare. The question that remains to be answered is which factors impact on the decision of university researchers to engage in consulting assignments? This paper contributes with an empirical analysis of this issue and is based on a survey of university professors in Germany and Sweden.
urn:nbn:de:hbz:1105-opus4-214
Keywords: 650; Forschungskooperation; Wissenstransfer; Unternehmensberatung